Produksi Nutrisi Hidroponik ABC Mix Hayati - Sesanti, Rizka Novi; Ali, Fahri; Darma, Wika Anrya; Tiara, Dede; Rahhutami, Ratih; Yeni, Yeni; Prajaka, Nanang Wahyu; Febria, Dila; Safitri, Betari; Hamiranti, Rahmadyah; Putri, Sekar Utami; Maulida, Desi (Journal of Horticulture Production Technology, 2024)
ABC mix biological hydroponic nutrition is an innovation by developing the AB Mix hydroponic nutrition formulation (based on 100% chemicals) in collaboration with Liquid Organic Biofertilizer/LOB from LOB Plant PT. Great Giant Pineapple (PT.GGP). This invention is created in order to solve the problem of industries that want to produce hydroponic nutrients based on liquid organic biological fertilizer to reduce the concentration of chemicals in hydroponic nutrients. The aim of this invention are (1) to develop hydroponic nutrient products consisting of chemical fertilizers and biological fertilizers so that the use of chemicals can be reduced, (2) to produce patents granted regarding hydroponic nutrition based on chemical fertilizers and biological fertilizers, and (3) to apply the results of the invention to society and industry that requires the invention. The ABC Mix biological hydroponic nutrition product already has a patent with number IDS000006120 and has been implemented at Miftahul Huda Islamic Boarding School 606 through community service activities.